The concept of a digital enterprise and its visualisation - Vučeković Miloš; Radović-Marković Mirjana; Marković Dušan (Trendovi u Poslovanju)
Digitization is moving most business processes into the virtual arena. The fact is that digitized companies and new concepts of organizational functioning are creating our new reality. Defining the meaning of the term digitalization creates a lot of controversy, which reflects the fact that it is a relatively new concept where there is no consensus and common understanding. Some of these controversies focus on whether the term should describe the use of digital technology to change certain business operations or create brand new business models. Notwithstanding these differences in approach, the aim of this paper is to show that digital transformation is an inevitability in contemporary business driven by the evolution of the new digital technology. Accordingly, the paper points to the specifics of the functioning of organization in terms of organizational structure, communication methods, employee agility and virtual team formation. It concludes that businesses that do not adapt quickly enough to new technologies that affect business and society can very quickly fall out of business because of product obsolescence.